Validation of automated pipetting systems for cell culture seeding, exposure and bio-analytical assays in sulfur mustard toxicology. (1st March 2020) - Rothmiller, Simone; Balszuweit, Frank; Menacher, Georg; Steinritz, Dirk; Kehe, Kai; Thiermann, Horst; Schmidt, Annette
Highlights: In vitro cell culture experiments as highly important techniques to accelerate drug discovery. Validation of two combined automated pipetting systems. 2 % technical imprecision for the cell survival assay and 4.5–6 % for the other assays. Intraday variations were much larger than technical variations. Assumption of intraday biological variability between the wells of an experimental group. Abstract: In vitro cell culture experiments are highly important techniques to accelerate drug discovery, conduct safety testing and reduce the need for animal studies. Therefore, automatization may help to enhance the technical precision, reduce external (including operator's) influence on the data and thus improve reliability. Prior to application in scientific studies, validation of automated systems is absolutely necessary. In this study we present the validation of two combined automated pipetting systems to conduct toxicity studies in HaCaT cells consisting of cell seeding, noxious agent exposure and several assays to assess cell survival, apoptosis and interleukin production. After initial validation of pipetting accuracy, we compared homogeneity after automated seeding to plates seeded by expert laboratory technicians. Moreover, automated dispensing of a potentially unstable noxious agent was analyzed in terms of speed and consistency. We found a 2 % technical imprecision for the cell survival assay and 4.5–6 % for the other assays, bioluminescent and ELISA techniques. Thus, we could demonstrate the excellent technical precision of our assays. In a final step, we found that intraday variations, though acceptable, were much larger than technical variations and had to assume an intraday biological variability between different wells of the same experimental group.